Resistance Media and Resistance Arts: A Study of “Survival Guide untuk Kampong Radioaktif” - Yow, Chong Lee; Mohd. Affendi, Azizan (Department of Media Studies, Faculty of Arts & Social Sciences, University of Malaya, 2016)
This paper is tailored to look into utilisation of films with resistance elements in mobilising people to participate in social movements which aim to bring about social changes, influencing public opinion and government policies. The authors are particularly fascinated by the anti-Lynas movement which managed to mobilise the people to demand the Australian rare-earth processing corporation, Lynas to stop its operation in Gebeng, Kuantan. To be precise, this article will delve into the films made via a film project entitled “Survival Guide untuk Kampung Radioaktif” initiated by a group of independent filmmakers in order to create spaces for discussion and therefore an informed decision. Two conceptions on resistance arts and resistance media developed by two different scholars, namely Jacques Rancière and Joshua D. Atkinson will be discussed in this paper in order to point out the possibility in combining these concepts to look at films with resistance elements. From there, the authors will employ framing analysis in their efforts to explicate the overarching theme and arguments woven in the chosen films in order to study their compatibility with the conception of resistance arts and media. Lastly, the authors observe and argue that there is a gap of scholarly understanding on both the resistance media and arts which needed to be addressed in future research.